2013
DOI: 10.1523/jneurosci.2136-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Paradoxically Augments Exocytotic Dopamine Release and Phasic Dopamine Signals

Abstract: Drugs of abuse hijack brain reward circuitry during the addiction process by augmenting action potential-dependent phasic dopamine release events associated with learning and goal-directed behavior. One prominent exception to this notion would appear to be amphetamine (AMPH) and related analogs, which are proposed instead to disrupt normal patterns of dopamine neurotransmission by depleting vesicular stores and promoting non-exocytotic dopamine efflux via reverse transport. This mechanism of AMPH action, thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
199
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(224 citation statements)
references
References 68 publications
24
199
1
Order By: Relevance
“…We found spontaneous dopamine transients in the DMS of sham-lesioned animals that increased following AMPH administration (Fig. 5E), in agreement with previous studies (31). In the 6-OHDAlesioned animals, spontaneous dopamine transients in the DMS ipsilateral to the SN lesion were not present under vehicle administration, but were elicited by AMPH administration (Fig.…”
Section: Stimulation Of Dopamine Neurons Elicits Release In the Contrsupporting
confidence: 92%
See 1 more Smart Citation
“…We found spontaneous dopamine transients in the DMS of sham-lesioned animals that increased following AMPH administration (Fig. 5E), in agreement with previous studies (31). In the 6-OHDAlesioned animals, spontaneous dopamine transients in the DMS ipsilateral to the SN lesion were not present under vehicle administration, but were elicited by AMPH administration (Fig.…”
Section: Stimulation Of Dopamine Neurons Elicits Release In the Contrsupporting
confidence: 92%
“…FSCV has been used to measure dopamine fluctuations in a number of studies; however, to date, all awake-animal measurements have been restricted to a single hemisphere (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(31)(32)(33)(34)(35). To investigate connectivity between hemispheres, we measured dopamine transients bilaterally in the NAc of freely moving rats.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs of abuse increase dopaminergic transmission in the NAc (Cheer et al, 2007;Daberkow et al, 2013;Di Chiara and Imperato, 1988;Phillips et al, 2003;Volkow et al, 2007), which contributes to their acutely reinforcing properties. We used a dose of morphine that, when paired with precipitated withdrawal, generates rapid dependence in rats (Schulteis et al, 1999).…”
Section: Morphine-exposure Increases Dopaminergic Transmission In Thementioning
confidence: 99%
“…5). Recently, it has become clear that, aside from these traditional mechanisms, amphetamines are also capable of modulating action potential-dependent neurotransmitter release (Branch and Beckstead, 2012;Daberkow et al, 2013). Furthermore, amphetamines regulate DA neurotransmission via inhibition of monoamine oxidase (MAO) and enhancement of tyrosine hydroxylase (TH) and have numerous other receptor targets, including the a2-adrenergic receptor, the sigma receptor, and the trace amine-associated receptor 1 (TA 1 ) receptor (Fung and Uretsky, 1982;Robinson, 1985;Ritz and Kuhar, 1989;Matsumoto et al, 2014;Reese et al, 2014).…”
Section: B Amphetamine-type Psychostimulantsmentioning
confidence: 99%
“…One study that examined this demonstrated that AMPH at 10 mg/kg enhanced electrically evoked DA release measured 10 and 30 minutes after the initial injection. Additionally, it was shown that a low dose (1 mg/kg) of AMPH facilitated the DA release associated with a rewarding stimulus cue, suggesting that AMPH acts, at least in part, by altering the characteristics of action potential-dependent exocytotic DA release (Daberkow et al, 2013). Unlike AMPH, MPH was recently shown to decrease exocytotic DA release (Federici et al, 2014), which may help explain the differing subjective effects of this drug.…”
Section: Comparison Of the Mechanisms Of Action Of Amphetamine Versusmentioning
confidence: 99%